A framework for the integration of lean, green and sustainability practices for operation performance in South African SMEs. Issue 1 (31st December 2022) - Thekkoote, Ramads
ABSTRACT: To make small and medium enterprises (SMEs) competitive, they not merely concentrate the results of the operational measures and combine the environmental dimension by adopting lean and green models together. The present literature study proves that lean activities in SMEs have a direct positive effect on green and sustainable practices. However, the combined effect of sustainable, lean, and green has not been investigated empirically. This paper aims to identify the relationship between lean, green, and sustainable practices for environmental development economic efficiency among small and medium-sized enterprises. The structural equation modelling technique was used to examine the direct effect of lean practices on sustainability, with green manufacturing as the mediating variable. The research depends on the collection of data from 210 manufacturing organisations. The result of the study indicates that lean practices directly affect sustainability and confirm that green manufacturing is a significant mediating parameter. These findings will be used to establish a comprehensive model for the sustainable lean, green system to direct small and medium-sized enterprises to achieve sustainable development. The research results can benefit in making the policies for industrial professionals on (SMEs) by focusing on critical issues to help implement and evaluate sustainable, lean, and green practices